2015
DOI: 10.1182/asheducation-2015.1.250
|View full text |Cite
|
Sign up to set email alerts
|

Is there a best TKI for chronic phase CML?

Abstract: The development of BCR/ABL1 tyrosine kinase inhibitors (TKIs) over the past 20 years has dramatically improved the outcomes for patients with every stage of Philadelphia chromosome-positive (Phϩ) chronic myeloid leukemia (CML). Clinicians now have access to 5 oral, generally well-tolerated, and highly effective TKIs. How should these agents be used for an individual patient to ensure the best possible duration and quality-of-life, to avoid treatment-related complications, and potentially to achieve a cure at a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…In the present study, EUTOS scores were not significantly different between cases that switched to 2G‐TKIs and those who continued with imatinib. However, for adult patients with a high Sokal score, starting treatment with either nilotinib or dasatinib has been recommended . 2G‐TKIs as first‐line treatment might bring therapeutic benefit to pediatric CP‐CML patients with some risk factors that have not yet been established.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the present study, EUTOS scores were not significantly different between cases that switched to 2G‐TKIs and those who continued with imatinib. However, for adult patients with a high Sokal score, starting treatment with either nilotinib or dasatinib has been recommended . 2G‐TKIs as first‐line treatment might bring therapeutic benefit to pediatric CP‐CML patients with some risk factors that have not yet been established.…”
Section: Discussionmentioning
confidence: 99%
“…Side effects from TKI therapy are rarely severe, and perhaps for that reason, their importance tends to be minimized by clinicians. However, low‐grade toxicities from a therapy that patients may need to continue indefinitely can impact adherence and thus overall outcome . In an International Randomized Study of Interferon versus STI571 (IRIS) study, adverse symptoms within 5 years of imatinib treatment were identified, which include fluid retention (61.8%), muscle cramps (50.0%), musculoskeletal pain (47.8%), and diarrhea (57.3%) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in both cases, there were no significant differences in survival compared to imatinib at 5 years follow-up 8. Bosutinib is currently being evaluated under the BELA trial (bosutinib vs imatinib) with promising results at 2 years 9. EPIC trial (ponatinib vs imatinib) was stopped prematurely due to unacceptable rates of arterial thrombotic events 9…”
Section: Discussionmentioning
confidence: 99%